2003
DOI: 10.1007/s00467-002-1056-2
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome associated with human parvovirus B19 infection

Abstract: A previously healthy 8-year-old Japanese boy developed nephrotic syndrome during the course of erythema infectiosum due to human parvovirus B19 (PVB19) infection. A renal biopsy showed mesangiocapillary proliferative glomerulonephritis with immune complex deposits associated with PVB19 virus. His renal involvement improved spontaneously.Keywords Parvovirus · Erythema infectiosum · Immune complex-type nephritis Case reportA previously healthy 8-year-old Japanese boy was admitted to Juntendo University Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…In some but not all cases studied, parvovirus antigens were localized to glomerular cells that were not further characterized [19, 23], but were entirely absent in six cases [25]. Thus, a major unresolved issue is the localization of parvoviral nucleic acid and protein within kidney tissue from individuals with parvovirus B19 infection; it is unclear whether this is due to methodologic or biologic differences or to inclusion of subjects lacking parvoviral infection or at different stages of glomerular disease evolution [26].…”
mentioning
confidence: 99%
“…In some but not all cases studied, parvovirus antigens were localized to glomerular cells that were not further characterized [19, 23], but were entirely absent in six cases [25]. Thus, a major unresolved issue is the localization of parvoviral nucleic acid and protein within kidney tissue from individuals with parvovirus B19 infection; it is unclear whether this is due to methodologic or biologic differences or to inclusion of subjects lacking parvoviral infection or at different stages of glomerular disease evolution [26].…”
mentioning
confidence: 99%
“…Our paediatric patient presented with urine abnormalities indicating nephritis. Notably, the association of parvovirus B19 infection with acute postinfectious glomerulonephritis has been earlier described in previously healthy children [1,7,12] and in children with sickle cell disease . Besides acute nephritic syndrome, clinical characteristics of previous case reports included systemic oedema and hypocomplementaemia [8] .…”
Section: Case Reportmentioning
confidence: 83%
“…Besides, studies have shown that the incidence of nosocomial infections increases significantly after 20 days of admission, and the general length of hospital stay is preferably controlled within 20 days. [ 3 ] So, minimizing the length of hospital stay and reducing the chance of contact with pathogenic bacteria are both good ways for children with PNS. While, the ratio cannot help us judge the specific details of the antibiotics use.…”
Section: Discussionmentioning
confidence: 99%